On the Infinite God Objection: a Reply to Jacobus Erasmus and Anné Hendrik Verhoef - Loke, Andrew Ter Ern (Sophia, 2016)
Erasmus and Verhoef suggest that a promising response to the infinite God objection to the Kalām cosmological argument include showing that (1) abstract objects do not exist; (2) actually infinite knowledge is impossible; and (3) redefining omniscience as (G): for any proposition p, if God consciously thinks about p, God will either accept p as true if and only if p is true, or accept p as false if and only if p is false. I argue that there is insufficient motivation for showing (1) and (2) and that (G) is problematic as a definition of omniscience.